The role of substituents in determining the redox potential of organic electrode materials in Li and Na rechargeable batteries: electronic effects vs. substituent-Li/Na ionic interaction (vol 7, pg 11438, 2019) - Lee, Sechan; Kwon, Ji Eon; Hong, Jihyun; Park, Soo Young; Kang, Kisuk (ROYAL SOC CHEMISTRY, 2020)
Correction for 'The role of substituents in determining the redox potential of organic electrode materials in Li and Na rechargeable batteries: electronic effects vs. substituent-Li/Na ionic interaction' by Sechan Lee et al., J. Mater. Chem. A, 2019, 7, 11438-11443.